A Conceptual Framework Regarding the Multicultural Education Competencies of Teachers - Acar Ciftci, Yasemin; Gurol, Mehmet (HACETTEPE UNIV, 2015)
While the traditional goal of education is to ensure students' socialization by getting them to accept existing ideologies, rules and practices in a country or society, the ultimate goal of multicultural education is to contribute to the establishment, application and maintenance of social justice and equality and thus ensure a social transformation. This perspective requires a drastic change in education system and curriculum. Moreover, the competencies teachers need to possess naturally differ in this paradigm and it becomes necessary to train teachers and teacher candidates in line with this understanding. The purpose of this study is to form a conceptual framework for critical multicultural education competencies that must be possessed by teachers that will work in multicultural environments. In this literature-based study aiming to establish the cultural competencies of teachers, three dimensions - each with 4 sub-dimensions - were determined and a conceptual framework was formed based on critical multicultural education theory, critical theory and critical race theories.
Keywords: critical multicultural education theory; critical theory; critical race theory; teachers' multicultural education competence; cultural competence; AFFIRMATIVE-ACTION; RACE; Education & Educational Research